Vision and Performance. The Sociolinguistic Analysis of Genres and Its Application to Focussed Ethnographic Data - Schnettler, Bernt (Qualitative Sociology Review, 2008)
The use of audiovisual recording devices is changing the practice of qualitative research. Extensive corpus of data can be generated in (shortterm) focussed fieldwork. Nevertheless, methods to analyse video data are still in an experimental stage. This article explores the benefits and limitations of applying sociolinguistic genre analysis to audio-visual data. This is illustrated with a case study, based on the videotaped »deep-trance vision« of a New Religious Movement’s spiritual leader, which is one the most famous contemporary religious visionaries in Germany. The analysis aims to reconstruct the construction of this religious experience of transcendence from the perspective of its followers. We will examine three different levels of communication (a) the inner context, exploring the textual, gestural, mimical and prosodic aspects, (b) the intermediate level where the focus lies on the setting and decorum, and finally (c) the outer context, focussing on the social embedding of this form of »transcendent« communication and its filmic presentation. The article closes with a reflection on the need to combine hermeneutic analysis of case studies based on textual analysis with ethnographic field data and observation to contextualise its interpretation.